2015
DOI: 10.1155/2015/105183
|View full text |Cite
|
Sign up to set email alerts
|

An Incarcerated Colon Inguinal Hernia That Perforated into the Scrotum and Exhibited an Air-Fluid Level

Abstract: There are few reports of a transverse colon inguinal hernia; furthermore, an inguinal hernia perforating the scrotum is rare. Here we report the case of a 79-year-old man who died after developing an incarcerated colon inguinal hernia that perforated the scrotum and exhibited an air-fluid level. The patient was referred to our hospital in November 2011 with a complaint of inability to move. Physical examination revealed an abnormally enlarged left scrotum and cold extremities. He reported a history of gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Combination of inguinoscrotal hernia and diverticulitis is a rare couple [1][2][3]. In acute scrotum, patient presents acute pain in scrotal bag or its content and could be followed by infl ammation, blush, oedema and size increase [3,4]. Cause of acute abdomen in this patient was a perforated diverticula with a previous inguinoscrotal hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of inguinoscrotal hernia and diverticulitis is a rare couple [1][2][3]. In acute scrotum, patient presents acute pain in scrotal bag or its content and could be followed by infl ammation, blush, oedema and size increase [3,4]. Cause of acute abdomen in this patient was a perforated diverticula with a previous inguinoscrotal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…PubMed's review (Table 1) of similar cases showed rarity of this clinical presentation, laparoscopic Hartmann's intervention is the most common [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Although free air in hernia sac has been reported in some case reports,[ 6 ] a specific term has never been used for this so we propose usage of the term “pneumohernios” (Gk., pneumon - lung, air; Gk., hernios - split, rupture) for clinical, radiological, or per-operatively demonstrable free air in any hernial sac as was evident in our case.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found less than 40 reported cases, and establish that complications is often seen in these cases, such as perforation or incarceration [5]. Only a few cases of colon cancer and inguinoscrotal hernias have been reported in the literature [5], [6], [7], [8], [9], [10], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%